Bariatric surgery as a long-term treatment for type 2 diabetes/metabolic syndrome - Nor Hanipah, Zubaidah; Schauer, Philip R. (Annual Reviews, 2020)
Metabolic surgery is increasingly becoming recognized as a more effective treatment for patients with type 2 diabetes (T2D) and obesity as compared to lifestyle modification and medical management alone. Both observational studies and clinical trials have shown metabolic surgery to result in sustained weight loss (20-30%), T2D remission rates ranging from 23% to 60%, and improvement in cardiovascular risk factors such as hypertension and dyslipidemia. Metabolic surgery is cost-effective and relatively safe, with perioperative risks and mortality comparable to low-risk procedures such as cholecystectomy, hysterectomy, and appendectomy. International diabetes and medical organizations have endorsed metabolic surgery as a standard treatment for T2D with obesity.